A swimmer`s classsification system based in kinematics, anthropometrics and hydrodynamics - Barbosa, Tiago M. (2013)
The aim of this paper was to identify active drag determinants and classify swimmers based on such features. 67 young swimmers made a maximal 25m Front-Crawl to measure with a speedo-meter the swimming velocity (v), speed-fluctuation (dv) and dv normalized to v (dv/v). Another two 25m bouts with and without a perturbation device were made to estimate active drag coefficient (CDa). Trunk transverse surface area (S) was measured with photogrammetric technique on-land and in the hydrodynamic position. Cluster 1 was related to swimmers with a high speed fluctuation (i.e., dv and dv/v). Cluster 2 was characterized by the anthropometrics (i.e., S). Cluster 3 was associated with the high hydrodynamic profile (i.e.,CDa). The variable that seems to discriminate better the clusters was the dv/v (F=53.680; P<0.001), followed by the dv (F=28.506; P<0.001), CDa (F=21.025; P<0.001), S (F=6.297; P<0.01) and v (F=5.375; P=0.01). Stepwise discriminant analysis extracted 2 functions. Function 1 was mainly defined by dv/v and S (74.3% of variance), while Function 2 was mainly defined by CDa (25.7% of variance). So, it can be concluded that kinematics, anthropometrics and hydrodynamic features are determinant domains to classify and characterize swimmers’ profiles.